Output, prices and productivity in Irish sheltered and exposed transportable goods industries, 1953-1967 - Hughes, JG (Economic & Social Studies, 1971)
In a paper on price and income determination in the Norwegian economy, Aukrust classifies industries as being either sheltered or exposed. He defines exposed industries as 'those which market their products abroad, or on the domestic market under strong foreign competition.' The exposed group therefore consists of export-oriented and import-competing industries. Sheltered industries are 'those industries whose products are marketed at home under conditions such as to leave them relatively free of foreign price competition'.
Keywords: Economy - Norway